Transparent, flexible, and conducting films based on graphene–polymer composites. Issue 1 (11th February 2016) - Singh, Bimal P.; Nayak, Sasmita; Nanda, Kamala K.; Singh, Anurag; Takai, Chika; Takashi, Shirai; Fuji, Masayoshi
Abstract : We present a simple solution‐based general approach for the preparation of flexible, transparent, and conducting composite films with molecular level dispersion of individual graphene nanosheets in the polymer [poly( N ‐hydroxymethyl) acrylamide] hosts via in situ polymerization. The graphene oxide (GO) concentration varies from 0 to 0.08 wt% in polymer matrix. The resulting composite film was characterized by FESEM, AFM, Raman, UV–vis spectroscopy and electrical measurement. The composite film has conductivity up to 10 −5 S m −1 and transmittance 90% at 550 nm respectively, which is adequate for many applications. These transparent conductive graphene bearing composite films presents a uniform, flexible, stable, and tailorable material. POLYM. COMPOS., 39:297–304, 2018. © 2016 Society of Plastics Engineers